Introduction: contentious women's empowerment in South Asia. Issue 4 (2nd October 2019) - Nazneen, Sohela; Hossain, Naomi; Chopra, Deepta
ABSTRACT: Questions of women's power remain a matter of heated debate globally, but take on a heightened intensity in a South Asia featuring rapid economic growth and structural transformation in recent decades. This Special Issue aims to improve understanding of how the women of South Asia are gaining and exercising power and of the obstacles and backlash they face, moving beyond discussion of women's empowerment as a matter of control over domestic economic resources or labour market participation. Articles from Bangladesh, India, Nepal, and Pakistan examine the struggles of garments workers in global value chains, middle class professionals, subsistence farmers and wage labourers, tracing the actors, institutions, and movements that build or block women's pathways to power. Collectively, the articles argue for paid work to be treated as a critical arena for struggles over women's power, not an end in itself. They draw attention to the roles of states and patriarchal forces in building or blocking pathways to power, and to the resilient nature of gendered norms that serve patriarchy. And they highlight the need for research into women's empowerment to focus on key episodes of political contention, as critical junctures for the progress – or retreat – of women's empowerment.